Biofortificação de arroz com zinco: quantificação e expressão gênica - Duarte, Rômulo Fredson (2015)
Zinc (Zn) is one of the most important micronutrients for humans, plants and animals. However, the consumption of food with low Zn concentration (e.g., rice cereal diets) can lead to human zinc deficiency. Thus, the use of the biofortification through the increasing of the grain zinc content, for instance, has been one of the most sustainable approaches to alleviate the Zn deficiency. In this study two experiments were conducted where we evaluated: a) the variation of Zn concentration in rice grain among accessions from Brazil through the determination by acid digestion followed by analyzes using atomic absorption spectrophotometer and dithizone staining method (DTZ); b) the Zn staining intensity in the rice grains by using the ImageJ software analysis; c) the genes involved in metal homeostasis through the gene expression analysis during different rice plant stages; d) the relative contribution of uptake and translocation of Zn from plant to grains using rice genotypes with different seed Zn concentration. The results of first experiment showed that using the DTZ staining method together with ImageJ software analysis led to the identification of the variation of Zn concentration in grains and between grains tissues (embryo, endosperm and aleurone layer) among the rice genotypes studied. This is an important finding for rice breeders interested in developing high-density Zn genotypes to solve the Zn deficiency problem among the world's population. Thus, we suggest this methodology as a rapid screening procedure for the development of potential rice germplasm in accumulating Zn. However, it would be interesting to test this methodology in a large set of rice genotypes aiming for further refined calibration. In the second experiment observed that the high density Zn genotypes are not the most Zn efficient genotypes, but they promoted higher grain Zn content, which can be associated to root-shoot Zn translocation. Analysis of gene expression by sqPCR identified OsZIP4 as the more expressed gene independently of the plant growth stages. Additionally, qPCR analysis showed also differences in relative expression levels in different plant tissues grown under Zn treatments. However, further investigations following a wide group of representative genotypes for studies with biofortification, and identify physiological characteristics favorable to Zn accumulation in the grain may be necessary.